Double electromagnetically induced transparency in a four-level lambda atomic system with Doppler broadening - Nguyen Huy, Bang; Le Van, Doai; Hoang Minh, Dong; Nguyen Thi Thu, Hien (Communications in Physics, 2023)
In this paper, we study the formation of two electromagnetically induced transparency (EIT) windows in a four-level lambda atomic system with Doppler broadening. The depth and the width of the EIT windows are easily changed by adjusting the intensity of the controlling laser fields. Meanwhile, the position of the EIT windows is also easily shifted by changing the frequency of the laser fields. In particular, by turning on or off one of the two coupling laser fields, the probe field response can be switched between one or two EIT window regimes, i.e., it is possible to switch between absorption and transparency regimes, and vice versa. In addition, our analytical model also allows one to investigate the influence of temperature (or Doppler width) on EIT windows, which is necessary for experimental observations as well as related applications at room temperature.